The Razor's Edge Sidi Larbi Cherkaoui's Rien de Rien - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2001)
Review of Sidi Larbi Cherkaoui's Rien de Rien. This little band gradually constructs a picture in words, flesh and sound of how individuals from different cultures and generations intersect, overlap and slip apart. PALABRAS CLAVE: Sidi Larbi Cherkaoui, Rien de Rien.